PENERAPAN FOOT MASSAGE DALAM MENURUNKAN NYERI SETELAH OPERASI SECTIO CAESAREA PADA IBU NIFAS DI RSUD DR. MOEWARDI SURAKARTA - Puji Lestari, Migut Dwi; Sari, Irma Mustika; Fitri, Alfida (JURNAL KESEHATAN KARTIKA, 2023)
Background; Childbirth by section caesarea (SC) is a caesarean section delivery performed by splitting with a slice in the mother's abdomen to remove the baby from the mother's abdomen, this can cause pain in the surgical wound. Pain can cause various problems for both mother and baby. The impact of pain on the mother, namely Activity Daily Living (ADL) and maternal mobilization is limited due to an increase in pain intensity when the mother moves. Foot massage is one of the non-pharmacological therapies that can help reduce pain in mothers. Objective; Knowing the results of the implementation of the provision of Foot Massage on postoperative pain Sectio Caesarea At Post Partum At RSUD Dr. Moewardi Surakarta. Method; The type of application carried out is descriptive in the form of a case study. Respondents used were 1 mother post section caesarea surgery. Instruments using observation sheets and questionnaires measuring pain scales using the Numeric Rating Scale (NRS). Results: the results of the implementation of foot massage on respondents 2 consecutive days, namely with a pain scale of 5 (moderate pain) down to a pain scale of 2 (mild pain). Conclusion; There is a development in the level of pain in respondents who are given foot massage therapy at Dr.Moewardi Surakarta Hospital.